PERANCANGAN PRODUK HANDBODY LOTION JERUK NIPIS - Marcelino Andrianto Sukardjono; Viktor Manuel Subagio; Siswi Astuti; anita (jurnal ATMOSPHERE, 2022)
To soften and keep the skin from drying out, you can use cosmetic products in the form of body lotion. In addition to moisturizing, the skin needs antioxidants to ward off free radicals which in this study used lime. The purpose of this research is to design a cosmetic product that can provide health benefits for the body, especially for skin health by formulating hand body lotion using lime as raw material and describing the manufacturing process and the planned supply chain. This Handbody Lotion product with herbal raw materials using citrus fruit extract will be represented by the Citrely brand (read: sitrilai) which stands for Citrus and Lovely. The calculation of the break-even point was reached when producing 260,000 bottles (packages) with a BEP percentage of 57.023%. Calculation of POT after tax is obtained, the capital will return in a period of 5.72 years.